Phonological intervention in Greek-speaking preschoolers with speech sound disorders: Implementing phonological similarity and density. - Petinou, Kakia (International Journal of Speech-Language Pathology, 2026)
Purpose: The study examined speech gains in three bilectal Cypriot-Greek speaking children with speech sound disorders. The study is based on theoretical frameworks that are on par with word-level characteristics and is motivated by the sparsity of cross-language studies in speech sound disorder intervention. Method: A multiple-baseline, single-participant design was implemented across three participants with speech sound disorders aged 3;2–4;0 years across baseline (pre-test), intervention, post-test, and follow-up phases. Intervention was administered twice a week for two months. Treatment stimuli were selected based on phonological density and phonological similarity grouped in word clusters. Outcomes were measured using a 49-word pictorial production probe list. Maintenance gains were examined with 20 non-treated stimuli during a follow-up session. Dependent variables included phonetic inventory size, proportion of consonants correct, and percentage of whole word matches. Intelligibility was measured via the Intelligibility in Context Scale. Result: Phonological gains were observed across all measures with effect sizes ranging from 1.2 to 2.7. Conclusion: Implementing phonologically dense stimuli may facilitate speech outcomes in children with speech sound disorders cross-linguistically.